A rapid review of Indigenous boys' and men's sexual health in Canada. Issue 5 (4th May 2021) - Hackett, Lisa; Biderman, Maya; Doria, Nicole; Courville, Julien; Bogner, Emma; Spencer, Rebecca; Miller, Dave; McMillan, Jane; Numer, Matthew
Abstract: Indigenous boys and men in Canada face adverse social and structural circumstances that affect their ability to achieve and maintain sexual health. Research about Indigenous sexual health, however, is largely limited to matters relating to women and statistics on sexually transmitted infections. A rapid review of research was conducted to determine what is currently known about Indigenous boys' and men's sexual health in Canada. Given the prevalence of research documenting quantitative disparities, the current review included qualitative research only. Thirteen included studies explored a wide range of topics relating to sexual health and an overarching intersection between social conditions and individual health outcomes was observed. The results of this review reveal significant gaps in the literature relating to the holistic sexual health of Indigenous boys and men and highlight important domains of sexual health to consider in future research. Findings suggest that sexual health programmes that promote traditional Indigenous knowledge and intergenerational relationships may be effective for promoting sexual health among Indigenous boys and men.